KINERJA, KENDALA, DAN STRATEGI PROGRAM KREDIT USAHA RAKYAT SEKTOR PERTANIAN MASA DEPAN - Rusli Burhansyah (Forum penelitian Agro Ekonomi, 2021)
Agricultural funding institutions need capital business. The challenge of the Agriculture Sector Public Credit Program is to increase reach program, institutional regulations, empowerment, and synergy. Some of the problems of the Agriculture Sector Public Program include low absorption rates, schemes, program coverage, assistance, and institutions. Policy recommendations among others; increase people business credit proposals agricultural, provide the people business credit scheme with a base and groups like the farmer's group, involving Agribusiness Micro Finance Institution and cooperatives, extending branch of the bank and the of a companion. Recommendations empowerment and synergies between other; addition and strengthening the role of Independent Smallholder Financing Facilitator, special programs the agricultural sector (people plantation and holder livestock) with the ceiling adjusted to the proposal, joint responsibility, business partner, Independent Smallholder Financing Facilitator in Sector Public Credit Program special enough important. Cooperation with the Field Agriculture Extension necessary for the socialization is at the farmer's group and gapoktan. The technical team's provincial and district role is to performance monitoring Independent Smallholder Financing Facilitator.